HHEX: A Crosstalker between HCMV Infection and Proliferation of VSMCs - Li, Lingfang; Liu, Meitong; Kang, Leitao; Li, Yifan; Dai, Ziyu; Wang, Bing; Liu, Shuiping; Chen, Liyu; Tan, Yurong; Wu, Guojun (Frontiers in Cellular and Infection Microbiology, 2016)
Objective：The study was designed to evaluate the role of Human cytomegalovirus (HCMV) infection on homebox (HOX) gene expression and the effects of overexpression of HOX genes on proliferation and apoptosis of vascular smooth muscle cells (VSMCs). Methods: Viral infection was verified by observation of cytopathic effects through inverted microscopy, viral particles by electron microscopy and HCMV IE gene amplification by RT-PCR. cDNA profiling technology was used to screen expression of HOX genes after HCMV infection in VSMCs. Abnormal expression of Haematopoietically-expressed homeobox (HHEX) was selected to construct over-expressed vector and transfected into VSMCs. The effects of over expression of HHEX on cell proliferation and apoptosis of VSMCs were assayed by flow cytometry. Apoptosis and proliferation-associated genes were also assayed by RT-PCR. Results: Multiple HOX gene expression levels had obvious changes after HCMV infection, among which expression of HHEX gene increased obviously at 24, 48 and 72 hours after infection. Over expression of HHEX can promote VSMCs proliferation by promoting G0 / G1 phase cells into S phase and inhibit VSMCs apoptosis. HHEX inhibited the expression of apoptosis-associated caspase 2 and caspase3 and promoted the expression of cell cycle-related genes such as CDK2 and CDK6, CyclinB2 and CyclinD2. Conclusion: HHEX over expression induced by HCMV infection closely associated with vascular proliferative diseases.